Toxic chemicals in computers: reloaded - Brigden, Kevin; Webster, Joe; Labunska, Iryna; Santillo, David (Greenpeace, 2007)
"There is growing concern over the use of hazardous chemicals in consumer goods, particularly with regard to electrical and electronic equipment. Some of these products, including computers, can contain heavy metals and other hazardous chemicals as constituents of their various components. The ongoing use of such chemicals has the potential to impact on the environment and human health as a result of the manufacture, use and disposal of these products. In 2006, Greenpeace found a range of hazardous chemicals in laptop computers available for purchase in Europe, prior to the introduction of legislation, known as RoHS, regulating the use of certain hazardous chemicals in electrical and electronic products in the EU. More recently, similar legislation has been introduced in China. This subsequent study was conducted by Greenpeace following the introduction of these laws, to investigate the presence of certain hazardous substances in a range of laptop computers available for purchase within the EU and other countries in Europe, in North and South America and in Asia."